PENGARUH INDEPENDENSI DAN KOMPETENSI AUDITOR TERHADAP KUALITAS AUDIT DALAM MENDETEKSI KECURANGAN DAN KEKELIRUAN PELAPORAN KEUANGAN (Studi Empiris Pada Auditor KAP Di Semarang) - WAWAN - SETIAWAN; WILLYANTO KARTIKO KUSUMO (Jurnal Dinamika Sosial Budaya, 2019)
Public Accounting Profession ( auditors ) are like " two eyes sword ", on the one hand the auditor must consider the credibility and ethics of the profession, but on the other hand also had to face the pressure of clients in a variety of decision-making auditors. If the auditor is not able to resist pressure from clients such as personal stress, emotional or the financial independence of auditors has been reduced and can affect the quality of the audit. This study aims to analyze the influence of empirical evidence and prove the experience, knowledge, long associated with the client, the pressure from the client, the auditor's study of colleagues ( peer review), and non-audit services provided by the Firm to audit quality. The samples are 79 respondents is 18 auditors contained in the firm in Semarang. As for answering the research hypotheses using multiple regression analysis, after testing the classical assumptions. Based on the results of this study concluded that the experience in performing the audit, the auditor's knowledge as well as a study of co-auditors (peer review) has a positive effect on audit quality. So the depth and breadth of knowledge of an auditor as well as more experience in auditing also the presence of a fellow peer auditors , the better the quality of audits conducted.